ELF - EMF correlation study on distance from Overhead Transmission Lines and acute leukemia among children in klang Valley, Malaysia - Ba Hakim A.S.; Abd. Rahman N.B.; Mokhtar M.Z.; Said I.B.; Hussain H. (Institute of Electrical and Electronics Engineers Inc., 2023)
Acute Leukemia has become the most common type of cancer among children below 15 years old in Malaysia. Yet, its main etiologies are unexplained, leading researchers to relate its occurrence to environmental factors. Therefore, residential proximity to Overhead Transmission Lines (OHTL) was considered as an environmental risk factor contributing in the occurrence of Acute Leukemia due to its magnetic fields production. The objective of this research paper is to investigate the correlation of Acute Leukemia and residential magnetic field exposure and proximity to OHTL. Distance was measured using Google Earth software and magnetic field exposure was assessed using a magnetic field survey meter. Subjects enrolled in this study were children below 15 years old who received their medical treatment in Universiti Kebangsaan Malaysia Hospital (HUKM) and Kuala Lumpur General Hospital (GHKL). Case subjects are children diagnosed with Acute Leukemia while control subjects are children diagnosed with other Acute Illnesses. The analysis showed that the correlation is statistically insignificant between Acute Leukemia and both variables: Residential Magnetic Field Exposure (OR 0.82, 95% CI: 0.33-2.00, p= 0.66, X2= 0.20), Residential Proximity (OR 0.88, 95% CI: 0.35-2.22, p= 0.80, X2= 0.068). In conclusion, it was found that residential proximity to OHTL does not constitute any risk to children's health. Additionally, other socioeconomic factors which are contributing in the occurrence of Acute Leukemia, makes any previously proved relationship subjected to chance or methodology misconduct. © 2014 IEEE.